2004
DOI: 10.1093/humrep/deh100
|View full text |Cite
|
Sign up to set email alerts
|

Safety issues in assisted reproduction technology: Should ICSI patients have genetic testing before treatment? A practical proposition to help patient information

Abstract: ICSI is a highly efficient treatment of male factor infertility and therefore increasingly used to treat infertile men successfully. However, when used to treat patients with a genetic cause for their infertility, there may be an increased risk for the offspring. Chromosome aberrations, Y chromosome microdeletions and CFTR (cystic fibrosis transmembrane conductance regulator) mutations alone may explain up to 25% of azoospermia and severe oligozoospermia. These genetic defects could be identified before treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 36 publications
0
20
0
2
Order By: Relevance
“…36,40 Karyotype analysis and Y-chromosome microdeletion screening have been recommended to be performed in men with nonobstructive azoospermia, because as many as 10 -15% of these patients have an identifiable abnormality. 39,41,42 Aittomäki et al 22 suggest that these tests should also be carried out in men with oligozoospermia below 5 Â 10 6 /ml. Although it has been suggested that karyotype analysis should, before ART, be performed even in normozoospermic men, because some aberrations (such as 47,XYY) can be found, 36 this is not a general recommendation.…”
Section: Genetic Diagnosis Of Male Infertilitymentioning
confidence: 99%
See 2 more Smart Citations
“…36,40 Karyotype analysis and Y-chromosome microdeletion screening have been recommended to be performed in men with nonobstructive azoospermia, because as many as 10 -15% of these patients have an identifiable abnormality. 39,41,42 Aittomäki et al 22 suggest that these tests should also be carried out in men with oligozoospermia below 5 Â 10 6 /ml. Although it has been suggested that karyotype analysis should, before ART, be performed even in normozoospermic men, because some aberrations (such as 47,XYY) can be found, 36 this is not a general recommendation.…”
Section: Genetic Diagnosis Of Male Infertilitymentioning
confidence: 99%
“…43 The deletions arise usually de novo, but are transmitted to all male offspring in ICSI. 22 New findings have shown that not every steroid sulphatase (STS) deletion in Y-chromosome causes male infertility. 37 The existence of a spermatogenesis-controlling factor(s), called azoospermia factor (AZF), in the long arm of the Y-chromosome was first based on identification of large deletions of this chromosomal area in azoospermic or oligozoospermic men.…”
Section: Genetic Diagnosis Of Male Infertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…3 For those with oligozoospermia, the actual sperm concentration is indicative of the potential presence of a genetic disorder, specifically a Y-chromosome microdeletion in those with ,1310 6 sperm ml 21 . 4 Overall, there is variation in reports of the frequency of abnormal karyotypes in infertile men, most estimating between 8% and 10%. [5][6][7] This variation persists when specifically looking for the Yq deletions, but it appears that 5%-10% of men with NOA or SO may have such a deletion.…”
Section: Introductionmentioning
confidence: 99%
“…The third and most likely cause of adverse outcomes is the non-natural selection of a single sperm (ejaculated or non-ejaculated) which may lead to the passage of genetic defects that have caused the male infertility in the first place. 4,14 It has been interesting to see over the years that most studies comparing ICSI with in vitro fertilisation (IVF) generally report no increased risks associated with ICSI over and above those associated with IVF in any particular outcomes for the offspring. [15][16][17][18][19] There has been a recent study from Norway reporting that ICSI pregnancies have a lower risk of iatrogenic moderate preterm delivery, than IVF pregnancies.…”
Section: Introductionmentioning
confidence: 99%